Nilai Pancasila Sebagai Jalan Keluar Dalam Menegakkan Kesetaraan Gender di Era Industri 4.0 - Zahra Asyifa; Fatma Ulfatun Najicha (RONTAL: Jurnal Keilmuan Pancasila dan Kewarganegaraan, 2023)
The Industry 4.0 era has brought about significant advancements in information and communication technology, but has also created economic inequality, especially for women. Women are at risk of losing their jobs due to automation and robotization, and face difficulties accessing traditionally male-dominated jobs. Therefore, it is crucial to ensure that gender equality is upheld in the Industry 4.0 era, to ensure that technological advancements benefit all citizens equitably, regardless of gender. One possible solution to this challenge is the application of Pancasila values as the moral foundation of the Indonesian nation. Pancasila values such as unity, democracy, social justice, and diversity can be applied in various aspects of life, including efforts to uphold gender equality. By internalizing these values, society can form attitudes and actions that respect and fight for gender equality, which can help balance technological advancements with human values. In particular, the workplace is a critical area where gender-based discrimination and biases can often occur. Companies can adopt policies that prioritize diversity and inclusivity in hiring and promotion processes, and develop training programs to raise awareness about the challenges and barriers that women face in the workplace. Such programs can help reduce biases a culture of respect.